In Vitro anticandidal efficiency of newly synthesized zinc oxide/chitosan/vancomycin nanocomposite using Bacillus Licheniformis compared to fluconazole - Abou-Dobara, Mohamed I; Baka, Zakaria AM; El-Salamony, Shimaa M; El-Zahed, Mohamed M (Asia-Pacific Journal of Science and Technology, 2026)
The zinc oxide/chitosan nanocomposite functionalized with vancomycin (ZnO/CS/VA), which acts as a novel anticandidal modifier, was prepared using an environmentally friendly technique. Zinc oxide nanoparticles (ZnO NPs) were biosynthesized using Bacillus licheniformis ATCC 4527 and then linked to chitosan (CS) and vancomycin (VA) through a green chemical method. Several methods were utilized to characterize the prepared nanocomposite. UV-Vis spectroscopy results indicated an absorption peak at 348 nm. Fourier transform infrared spectroscopy (FTIR) and X-ray diffractometer (XRD) analyses demonstrated that the material matrix of the nanocomposite included ZnO NPs and various active groups. Transmission electron microscopy (TEM) images showed that the ZnO/CS/VA nanocomposite was spherical-shaped with a size range of 56-80 nm. The anticandidal effect of ZnO/CS/VA, used as a modifier to enhance antimicrobial activity, was tested against Candida albicans ATCC 10231. ZnO/CS/VA exhibited significant anticandidal activity in the agar well-diffusion test, minimum inhibitory concentration (MIC), and minimum fungicidal concentration (MFC) compared to the standard drug fluconazole. As the ZnO/CS/VA dose and the anticandidal inhibition increased, the antimicrobial activity became reliant on the nanocomposite dose. Five μg/mL was enough to cause complete biocidal action against Candida albicans, while 25 μg/mL of fluconazole was required. TEM micrographs of ZnO/CS/VA-treated Candida albicans showed various malformations and distortions in cell structure, including damage to the cell wall and the presence of vacuoles, indicating its potent antimicrobial effects. The results suggest that the combination of zinc oxide/chitosan nanocomposite and vancomycin could serve as an effective biomaterial for antifungal treatment and other medical applications.